If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2y + 6y + -1x = 0 Reorder the terms: 4x + -1x + -2y + 6y = 0 Combine like terms: 4x + -1x = 3x 3x + -2y + 6y = 0 Combine like terms: -2y + 6y = 4y 3x + 4y = 0 Solving 3x + 4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 3x + 4y + -4y = 0 + -4y Combine like terms: 4y + -4y = 0 3x + 0 = 0 + -4y 3x = 0 + -4y Remove the zero: 3x = -4y Divide each side by '3'. x = -1.333333333y Simplifying x = -1.333333333y
| 3t=t+6 | | x*0.06+x=950 | | a^2+1= | | (4w^2-6w-1)+(3w^2-7w+5)=0 | | x*0.06+x=800 | | (a-1)(a-1)= | | 5744406811=0 | | x*0.06+x=100 | | 4x^5-20x^4-35x^3-31x^2-9x+9=0 | | 3m+12=24 | | f(x)=7x^2+42x | | 2(-x+2y-11)= | | -4(x+y-8)= | | X+4.3=8.9 | | 20x+12y=24 | | 5(3x-10)= | | -7(1+4x)= | | 16z-32+9=2z+86 | | 8(5-4x)= | | 37803/x=0.75 | | 149388/x=0.73 | | xsqure+9=0findx | | -2m+9-4m-13= | | 6x-15-4x-(-8)= | | -14b+7y-5b-10y= | | -11g+8h-3g-7h= | | -7w-6k+4w= | | -8m+3+10+3m= | | 9917/X=0.74 | | (x+30)(x-3)=40 | | 68=-16t^2+80t+4 | | 32/X=0.32 |